Pengelolaan Pembelajaran Berbasis Lingkungan Sekolah dalam Meningkatkan Mutu Pembelajaran - Margarini, Yuli Dwi Bina; Verina, Ika; Nurfuadi, Nurfuadi (Fakultas Keguruan dan Ilmu Pendidikan, Universitas Muhammadiyah Kupang, 2026)
A conducive learning environment is an important foundation in creating a quality and meaningful learning experience. However, many schools still face challenges in designing learning environments that are adaptive to the diverse needs of students, which ultimately results in low levels of student engagement. This article aims to examine strategic approaches in the management of the learning environment in schools as an effort to improve student engagement and learning quality holistically. This study uses a literature study method or literature review by analyzing various theories and the latest research results regarding learning environment design, educational psychology, and classroom management. The results of the study show that effective management of the learning environment is not only limited to physical aspects (such as classroom layout and facilities), but also includes psychosocial aspects (safe and supportive classroom climate) and digital aspects (use of learning technology). Through an integrated and data-driven approach, schools can create a learning atmosphere that is not only engaging but also effective in improving student learning outcomes. This research is expected to provide insights and recommendations for educators and school managers in developing an optimal learning environment.